Wedge resection on recurrent pneumothorax, failed lung expansion after needle aspiration: A case report. (June 2021) - Charisma, Anita Nur; Bakhtiar, Arief
Abstract: Background: Pneumothorax has several classifications, including based on etiology, location, extent, and degree of collapse as well as by mechanism and type. Case presentation: A 61-years-old man with the main complaint of sudden shortness of breath after lifting a birdcage. The complaint worsened, and it was accompanied by nausea, sweating, and decreased vital signs. The patient was in a life-threatening condition with a tension pneumothorax and treated with needle aspiration (NA). On the second day of treatment, a clinical evaluation showed recurrent dyspnea. Lung physical examination and chest X-ray evaluation showed recurrent pneumothorax with subcutaneous emphysema. Installation of chest tube drainages (CTD) with active continuous suction of −20 cmH2 O. High-resolution CT (HRCT) showed right pneumothorax with multiple blebs, bullae, and bronchopleural fistula. Video-assisted thoracic surgery (VATS) was carried out to repair bronchopleural fistula (BPF). However, pre-surgery found multiple bullae and multiple fistulas accompanied by adhesion to the chest wall, thus the procedure could not be conducted. As an alternative, thoracotomy was performed, followed by wedge resection and fistula reparation. Discussion: Diagnosis of pneumothorax is based on clinical manifestations. Conservative management by providing oxygen or NA/CTD insertion. Needle aspiration is a simple and alternative treatment and performed for an outpatient indication, whereas CTD requiring hospitalization and is performed by experts. Management aims to restore clinical symptoms, restore lung expansion and prevent a recurrence. Conclusion: The choice of thoracoscopy/VATS or thoracotomy needs to be considered according to the indications so that complications do not occur and have a good prognosis. Highlights: The success rate of NA in pneumothorax is 60.65%. Needle aspiration is the first recommended course of action for the management of spontaneous pneumothorax. Complications in pneumothorax can be found BPF and also cause PAL. VATS is generally used for PAL and BPF management to identify and seal area of air leak.